Passeur de sens. Étude sémiotique sur la représentation du visage criminel dans Détective (1936) et Nouveau Détective (2014) - Maxime Fabre (Criminocorpus)
This publication proposes questionning the reprentation of criminals' faces through a comparative study of miscellaneous newspapers, such as Détective (1936) and Nouveau Détective (2014). By using a semiotic method on the concept of « face », the author defines two different types of « faceity » (viséagité). The device of Détective offers a social layout of criminals' faces through investigations stories, whereas Nouveau Détective elaborates a clever process of stigmatisation of the said faces.